Effect of salinity on the morphological, physiological and biochemical properties of lettuce (Lactuca sativa L.) in Bangladesh - Ahmed Sium; Ahmed Shawon; Roy Swapan Kumar; Woo Sun Hee; Sonawane Kailas Dashrath; Shohael Abdullah Mohammad (Open Agriculture, 2019)
This study aimed to explore the changes in morphological, physiological and biochemical characteristics of lettuce (Lactuca sativa L.) in response to salt stress when grown using hydroponic techniques. The seedlings were subjected to five different concentrations (0 mM, 50 mM, 100 mM, 150 mM, and 200 mM) of NaCl for three weeks. During the salt stress, morphological properties (shoot length, root length, total plant weight, leaf number) were measured in every week. After 21 days of salt stress, physiological properties (water content and relative water content) and biochemical properties (proline, protein, phenol, reducing and non-reducing sugar content) were measured. Morphological and physiological properties were found decreased gradually with increasing salt concentrations. Biochemical properties such as proline and protein content increased remarkably, and total phenol content decreased gradually with increasing salt concentrations. Reducing sugar accumulation was higher in all treatments except 50 mM in comparison to control. Non-reducing sugar accumulation was decreased in 100 mM and 200 mM treatment, similar in 150 mM treatment, and increased in 50 mM treatment when compared to control. These findings render lettuce a salt-sensitive plant at higher salt concentration. However, changes in characteristics were realistic up to 50 mM salt concentration.